Cognitive Demands And the EFL Writer: Observations on Kind, Degree, and Agency - Gómez González, Juan David (Íkala, Revista de Lenguaje y Cultura, 2014)
Research into understanding the process through which EFL writers revise texts have centered on matters of degree: of cognitive capacity and complexity or volume of tasks. This essay explores some of the junctures between dual process theories and EFL composition, and argues that questions of kind can be as pertinent. It aims to show that the kind of cognitive processes involved in revision often define what information the writers process, how they do so, and how they feel about their decisions.